Immigrants Move Where Their Skills Are Scarce: Evidence from English Proficiency - Ainhoa Aparicio Fenoll; Zoë Kuehn (Institute of Labor Economics (IZA), 2018)
This paper studies whether individuals tend to migrate to countries where their skills are scarce or abundant. Focusing on English language skills, we test whether immigrants who are proficient in English choose to move to countries where many or few individuals speak English. We use the introduction of English classes into compulsory school curricula as an exogenous determinant for English proficiency of migrants of different ages, and we consider cohort data on migration among 29 European countries, where English is not the official language and where labor mobility is essentially free. Our estimation strategy consists of refined comparisons of cohorts, and we control for all variables traditionally included in international migration models. We find that immigrants who are proficient in English move to countries where fewer individuals speak English, and where hence their skills are scarce. We also show that similar results hold for general skills.
Keywords: F22; I20; J24; J61; 330; migration; English language skills; choice of destination country